Microvesicles Derived from Human Embryonic Neural Stem Cells Inhibit the Apoptosis of HL-1 Cardiomyocytes by Promoting Autophagy and Regulating AKT and mTOR via Transporting HSP-70 - Lei Zhang; Jianyi Gao; Tianyan Chen; Xiang Chen; Xianyan Ji; Kai Ye; Jiahong Yu; Bin Tang; Yusheng Wei; Hong Xu; Jiabo Hu (Stem Cells International)
Myocardial reperfusion injury (MRI) induced by cardiomyocyte apoptosis plays an important role in the pathogenesis of a variety of cardiovascular diseases. New MRI treatments involving stem cells are currently being developed because these cells may exert their therapeutic effects primarily through paracrine mechanisms. Microvesicles (MVs) are small extracellular vesicles that have become the key mediators of intercellular communication. MVs derived from stem cells have been reported to play an important role in MRI. In this article, we attempted to explore the mechanisms by which MVs derived from human embryonic neural stem cells (hESC-NSC-derived MVs) rescue MRI. hESCs were differentiated into NSCs, and MVs were isolated from their supernatants by ultracentrifugation. H2O2 was used to induce apoptosis in HL-1 cardiomyocytes. Cell viability was detected by using the CCK-8 assay, apoptosis was detected by Annexin V-FITC/PI staining, and apoptosis-related proteins and signalling pathway-related proteins were detected by western blot analysis. Autophagic flux was measured using the tandem fluorescent mRFG-GFP-LC3 assay. Transmission electron microscopy and western blot analysis were adopted to evaluate autophagy levels. hESC-NSC-derived MVs increased the autophagy and inhibited the apoptosis of HL-1 cells exposed to H2O2 for 3 h in a dose-dependent manner. Additionally, hESC-NSC-derived MVs contained high levels of heat shock protein 70 (HSP-70), which can increase the level of HSP-70 in cells. Moreover, the same effect could be achieved by heat shock preconditioning of HL-1 cells overexpressing HSP-70. The benefits of NSC-MVs may be due to the involvement of AKT and mTOR signalling pathways. Importantly, hESC-NSC-derived MVs stimulated the activation of the AKTand mTOR signalling pathway in those cells by transporting HSP-70. Our results suggest that hESC-NSC-derived MVs inhibit the apoptosis of HL-1 cardiomyocytes by promoting autophagy and regulating AKT and mTOR via transporting HSP-70. However, this hypothesis requires in vivo confirmation.